(untitled) (CIPEEX, 2025)
The elderly person with diabetes mellitus experiences a reduction in muscle mass, which increases the risk of falls, thereby heightening the fear of falling. The objective of this work is to conduct an integrative literature review that can analyze the relationship between Type 2 Diabetes Mellitus, postural balance, and the risk of falls in the elderly. The databases PubMed, Scopus, LILACS, and SciELO were consulted, using the terms "Type 2 Diabetes Mellitus," "postural balance," "falls," "elderly," and "balance and elderly"; "balance and elderly and falls"; "balance and elderly and falls and diabetes mellitus." The inclusion criteria defined for the selection of articles were articles published in Portuguese and English, full-text articles that addressed the theme related to the integrative review, and articles published and indexed in the aforementioned databases. Elderly people with type 2 diabetes have a greater fear and risk of falls, and postural balance problems, especially those who use insulin or other medications.